Assessing the suitability of the South African Rock Art Digital Archive for the purpose of geocoding Rock Art sites - Chokoe, Bellina (My University, 2021)
The South African Rock Art Digital Archive (SARADA) is a repository of memory and a testament to over 30.000 years of human activities including interactions between people and the environment across the African continent. This archive is of great value to the African history and cultural depictions. However, incomplete information related to suitable geographic coordinates present a challenge for locating and accessing a considerable number of rock art sites, in this case considering the 780 rock art sites without geographic coordinates. This study assesses information records of rock art sites contained in SARADA to extract suitable textual information that can be used for the purpose of geocoding rock art sites. Geocoding methods are useful in transforming textual information into geographic coordinate locations. In order to determine whether the extracted textual information from SARADA was suitable for the purpose geocoding, attribute accuracy and completeness were assessed. Three standard geocoding methods were explored: Geocoding using addresses, geocoding using postal codes and geocoding using administrative boundaries. The textual information about rock art sites extracted from SARADA only allowed the geocoding of rock art sites to be performed at the postal code level (i.e. zip codes as geographic identifiers). The geocoding match rate is 62% which geocoded at a road level.
A research report submitted in partial fulfilment of the requirements for the Degree of Master of Science to the Faculty of Science, School of Geography, Archaeology & Environmental Studies, University of the Witwatersrand, Johannesburg. 2021